If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + -10 = 60 Reorder the terms: -10 + 7a = 60 Solving -10 + 7a = 60 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 7a = 60 + 10 Combine like terms: -10 + 10 = 0 0 + 7a = 60 + 10 7a = 60 + 10 Combine like terms: 60 + 10 = 70 7a = 70 Divide each side by '7'. a = 10 Simplifying a = 10
| 2(7+1)= | | 1/1/6*(1/34+1/34+1/22+1/27+1/45+1/55)=x | | 8-3x=kx | | -4(1+3)=-4*1+(-4)*3 | | 5(-3x+8)=40-15x | | 3y^2-10=20 | | 3(4x-2)-3=12x-9 | | 5x+4=7(x-3)+17 | | 2x^2+2x-5=0 | | t+0.23=56 | | 2+13=17 | | 35=70-7x | | 5(-3x+8)= | | 3*7=7*3 | | sqrt(7x-6)-2=3x-24 | | 6(a+5)=5(a+6)-6 | | y=11x+9 | | (x-1)+31=4x | | 78-29n=4n-35n | | y=-1.5x+8 | | -6(x+3)+90=3x-9(x-6) | | w^2-6w-64=0 | | 4(n+14)-3=292 | | 66=3y-17 | | 2a+44+(a+10)=180 | | 10(z+1)-4(z-1)=2(z-2)+3(z-3) | | 27x+4=18x+1 | | 10(z+1)-4(z-1)=2(z-2)+(z-3) | | 10-3x=24+4x | | 13(3x-5)=6x-4 | | 20+r=r-2(3r+3) | | 5a-b=1 |